The main tendencies of the current reform of the Ukrainian legislation in the field of health care - M. A. Anishchenko (Zaporozhye State Medical University, 2020)
The purpose of the research - to study the basic development directions of the legislation of Ukraine in the field of health care, to identify problems of reformation of the above legislation, to outline ways of their solution. Materials and methods. Regulatory framework of Ukraine, method of analysis, method of synthesis, comparative-legal method, structural-system method. Results. The main tendencies of the current reform of the legislation in the field of health care are the following directions of its development: change of the concept of financing of health care institutions, the digitization of the health care sphere, improvement of the system of transplantation of anatomical materials to a person, change of requirements to the professional competencies of executives of health care institutions. increase public health impact, increase access to medicines and blood components for patients, increase anti-corruption requirements for healthcare facilities. In addition, there is an attempt to introduce self-government. Conclusions. In spite of the positive tendencies in the overall reform of the health care legislation, there are some problems with its transformation, which need urgent resolution at the legislative level. Thus, when reforming the financial legislation in the field of health care, it is necessary to remember the norms of the Constitution of Ukraine, which say that the current network of health care institutions cannot be reduced. In addition, it is necessary to develop a package of amendments to the legislation, which should clearly regulate the implementation of medical and diagnostic work of scientific and scientific-pedagogical workers of institutions of higher (postgraduate) medical education and medical research institutions in the conditions of modern healthcare transformation, because such work is a prerequisite for ensuring educational and scientific processes. There is also a need to expand the introduction of health digitization, including for the purpose of fixing acts of will, which is very relevant in the context of providing informed consent to medical intervention by a patient or his legal representative. In addition, we believe that in the current conditions of development of medical education, the granting of access to the medical professions based on the decisions of medical self-government bodies is inappropriate.